Electron temperature dependence of the electron-phonon coupling strength in double-wall carbon nanotubes - Chatzakis, Ioannis (My University, 2013)
We applied Time-Resolved Two-Photon Photoemission spectroscopy to probe the electron-phonon (e-ph) coupling strength in double-wall carbon nanotubes. The e-ph energy transfer rate G(Te, Tl) from the electronic system to the lattice depends linearly on the electron (Te) and lattice (Tl) temperatures for Te>ΘDebye. Moreover, we numerically solved the Two-Temperature Model. We found: (i) a Te decay with a 3.5 ps time constant and no significant change in Tl; (ii) an e-ph coupling factor of 2 × 1016 W/m3; (iii) a mass-enhancement parameter, λ, of (5.4 ± 0.9) × 10−4; and (iv) a decay time of the electron energy density to the lattice of 1.34 ± 0.85 ps.